A Comprehensive Analysis Identified the Key Differentially Expressed Circular Ribonucleic Acids and Methylation-Related Function in Pheochromocytomas and Paragangliomas - Yu, Anze; Li, Minghao; Xing, Changsheng; Chen, Danlei; Wang, Cikui; Xiao, Qiao; Zhang, Liang; Pang, Yingxian; Wang, Yong; Zu, Xiongbing; Liu, Longfei (Frontiers in Genetics, 2020)
We investigated differentially expressed circular RNAs (circRNAs) and their potential functions in pheochromocytomas and paragangliomas (PCC/PGLs). Expression levels of circRNAs in tumor and adjacent normal tissues from seven PCC/PGL patients were analyzed through RNA sequencing. Real-time PCR was conducted to verify the key candidates identified in the sequencing data. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed to predict the functions of these circRNAs. A total of 367 circRNAs were found differentially expressed between tumor and normal samples. The top three histone methylation-related circRNAs (hsa_circ_0000567, hsa_circ_0002897, and hsa_circ_0004473) and their target microRNAs (miRNAs) were identified and validated. We then mapped the circRNA-miRNA-messenger RNA (mRNA) coding-noncoding gene co-expression (CNC) networks to show the potential binding relationships between circRNAs and their targets in PCC/PGLs. The top five mRNAs, 88 miRNAs, and 132 circRNAs related to pathogenesis were utilized to map the CNC network, and we observed that the interactions of these candidates with their target miRNAs regulated histone methylation and further mediated PCC/PGL pathogenesis. This study is the first to provide the whole profile of differentially expressed circRNAs in PCC/PGLs. Our data indicate that altered circRNAs may control the pathogenesis of PCC/PGLs by regulating histone methylation processes, highlighting their role as potential biomarkers.